Lidar remote sensing and applications - Dong, Pinliang; Chen, Qi; CRC Press (Boca Raton, FL : CRC Press, 2017)
LiDAR (Light Detection and Ranging) is a remote sensing technology that measures distance by illuminating a target with a laser and analyzing the reflected light. This book introduces the fundamentals of LiDAR remote sensing, LiDAR data processing and analysis methods and applications of LiDAR in forestry and vegetation mapping, urban environments, and geosciences.
chapter 1 Brief Overview of Remote Sensing / Pinliang Dong -- chapter 2 Principles of LiDAR Remote Sensing / Pinliang Dong -- chapter 3 Basics of LiDAR Data Processing / Pinliang Dong -- chapter 4 LiDAR for Forest Applications / Pinliang Dong -- chapter 5 LiDAR for Urban Applications / Pinliang Dong -- chapter 6 LiDAR for Geoscience Applications / Pinliang Dong.
Keywords: Ecology -- Remote sensing; Forests and forestry -- Remote sensing; Geography -- Remote sensing; Optical radar; Remote sensing